PENERAPAN TEKNIK ECOPRINTING DALAM GERAKAN SEKOLAH BERSIH MENYENANGKAN UNTUK MENGUATKAN PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Andayani; Monika Handayani; Ade Mardiana; Purwanti Pahrurodji (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2021)
This service is motivated by the existence of the Fun Clean School Movement (GSBM) which is integrated to shape the character of children to become religious, independent, and intelligent individuals like the motto of the City of South Tangerang. Meaningful education does not only think about scientific thinking, but needs to be integrated with characters that include various aspects of supporting the skills of elementary school-aged children. This service aims to provide an understanding of the concept of learning arts, culture and crafts in elementary schools whose development target is elementary school age. Combining the theory of development of elementary school-aged children, it was found that the learning content in the subjects of arts, culture and crafts can develop character in children through the scope of ecoprinting material. The stages of implementing this community service activity include: 1) Planning, 2) Implementation (training, mentoring and practice), 3) Evaluation. This service resulted in learning designs for Cultural Arts and Crafts, especially ecoprinting techniques in various media to support the Fun Clean School Movement (GSBM) program in strengthening KDP and the effectiveness of integrating arts and crafts learning in various media in supporting the Fun Clean School Movement (GSBM) as one of the ways to support character education.